Differential expression of tick Ixodes ricinus genes induced by blood feeding or infection: genetic analysis of ML domain containing proteins - Plchová, Jana (Jihočeská univerzita, 2012)
ML (MD-2-related lipid-recognition) domain containing proteins are recognized as immune-related molecules. They do not belong among well-studied proteins in ticks although their occurence is quite often. Generally, ML proteins are involved in innate immunity processes, lipid binding and transport. Usually, expression of tick ML domain containing proteins is induced by blood feeding. Two members of the ML protein family, ML-domain containing protein and Der-p2 allergen-like protein were isolated from Ixodes ricinus and characterized for the first time.
Differential expression of tick Ixodes ricinus genes induced by blood feeding or infection: genetic analysis of ML domain containing proteins
Keywords: tick; Ixodes ricinus; ML (MD-2 related lipid-recognition) domain; tick; Ixodes ricinus; ML (MD-2 related lipid-recognition) domain